2018
DOI: 10.1108/acmm-03-2017-1778
|View full text |Cite
|
Sign up to set email alerts
|

Improving the high-temperature oxidation resistance of ASME-SA213-T11 boiler tube steel by plasma spraying with CNT-reinforced alumina coatings

Abstract: Purpose This paper aims to discuss that a conventional Al2O3, 1.5 Wt.% carbon nanotubes (CNTs)-Al2O3, 2 Wt.% CNTs-Al2O3 and 4 Wt.% CNTs-Al2O3 composite coatings were deposited with the help of Plasma spray process. Design/methodology/approach To better understand the effect of CNT reinforcement on oxidation resistance, high-temperature oxidation behaviour of conventional Al2O3, 1.5 Wt.% CNTs-Al2O3, 2 Wt.% CNTs-Al2O3 and 4 Wt.% CNTs-Al2O3 composite coatings at 900°C was compared with the performance of the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Because CNTs helped bridging between splat boundaries which further resulted in reduced weight and volume loss of plasma sprayed hydroxyapatite-carbon nanotubes composite coating. Goyal et al [29] investigated hot oxidation performance of alumina, 1.5, 2 and 4 wt-% CNT-Al 2 O 3 composite coatings deposited by the plasma spraying method on T11 (ASTM-SA213-T-11) boiler steel at 900°C. It was observed that CNT reinforced coatings enhanced high-temperature corrosion resistance compared with conventional alumina coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Because CNTs helped bridging between splat boundaries which further resulted in reduced weight and volume loss of plasma sprayed hydroxyapatite-carbon nanotubes composite coating. Goyal et al [29] investigated hot oxidation performance of alumina, 1.5, 2 and 4 wt-% CNT-Al 2 O 3 composite coatings deposited by the plasma spraying method on T11 (ASTM-SA213-T-11) boiler steel at 900°C. It was observed that CNT reinforced coatings enhanced high-temperature corrosion resistance compared with conventional alumina coatings.…”
Section: Introductionmentioning
confidence: 99%
“…But, during the subsequent cycles of exposure, the oxide layer could not bear the strain and peeled off followed by cracks from the surface of the substrate as clearly visible in the macrograph [Figure 2 (b)]. The molten salt enters through the perpendicular cracks to reach towards the substrate, as observed by Goyal et al (2018a, 2018b), Chatha et al (2012) and Mehta et al (2017). The formation of un protective oxide was confirmed by XRD and EDS analysis followed, by the EPMA technique, which revealed that the thermal spallation and cracks in the scale might be attributed to formation of un protective Fe 2 O 3 and Cr 2 O 3 oxide scale.…”
Section: Discussionmentioning
confidence: 90%
“…The iron-based materials experienced extensive attack and more weight in the molten salt (Na 2 SO 4 – 60 Wt.% V 2 O 5 ) conditions as observed by Goyal (2018a) and Sidhu and Prakash (2005). Due to weight gain, the formation of oxides of Na and V caused penetration of oxygen towards the substrate, resulting in severe corrosion of base material (Goyal et al , 2018a; Rani et al , 2017). The corrosion rate of un-coated T-91 steel specimen increased during the initial cycles of study, which could be attributed to the formation of cracks in the upper layer of substrate.…”
Section: Discussionmentioning
confidence: 99%
“…30 Goyal et al reported CNT additions in aluminium dispersed homogeneously in coatings, chemically stable properties and decreased porosity with increasing CNT percentage deposited by plasma spray. 31…”
Section: Introductionmentioning
confidence: 99%
“…30 Goyal et al reported CNT additions in aluminium dispersed homogeneously in coatings, chemically stable properties and decreased porosity with increasing CNT percentage deposited by plasma spray. 31 Bhatia et al reported on the 65Cr 3 C 2 -35(Ni-20Cr) coatings, working under incinerated elevated situations. The Cr 3 C 2 hard phase in the NiCr matrix enhances erosioncorrosion resistance.…”
Section: Introductionmentioning
confidence: 99%